Factors influencing illness uncertainty in parents of children with congenital adrenal hyperplasia in a developing country: A cross-sectional study - Irene Astrid Larasati; Fanti Saktini; Tri Indah Winarni; Annastasia Ediati; Agustini Utari (Belitung Nursing Journal, 2023)
Background: Illness uncertainty in parents of children with congenital adrenal hyperplasia (CAH) refers to parents’ inability to create meaning in events related to their children having CAH. This may influence their role in caring for children with CAH. Objective: The study aimed to determine factors associated with illness uncertainty experienced by parents of children with CAH in a developing country. Methods: A cross-sectional study was conducted on 80 parents (43 mothers and 37 fathers) of children with CAH, selected using consecutive sampling methods. The Parent’s Perception of Uncertainty Scale (PPUS) was used to measure the illness uncertainty levels. Data were collected from March 2020 to October 2020. Independent t-test and chi-square test were used to determine factors (parent’s gender, age, educational level, monthly household income, number of children with CAH, history of child death due to CAH, child’s age when first diagnosed with CAH, duration of therapy, gender change, type of CAH (salt wasting/SW or simple virilizing/SV), current gender, and genitoplasty) influencing illness uncertainty in parents. Results: The mean scores of PPUS were 42.3 ± 12.91, and the majority of parents had a low PPUS score (49; 61%). Parents of children with SW-CAH showed higher uncertainty (44.2 ± 12.77) than those with SV-CAH (32.6 ± 8.86; p = 0.003). Parents who lost their children due to CAH were more likely to report a moderate illness uncertainty than parents who never experienced child mortality due to CAH (χ2(1, 80) = 4.893; p = 0.027). Conclusion: The factors significantly affecting uncertainty in parents of children with CAH determined in this study might help healthcare professionals, including nurses, to play a pivotal role in giving pertinent information regarding their children’s health, disease, and therapy to help manage parental uncertainty.